Poleward Propagation of Typhoon-Induced Near-Inertial Waves in the Northern South China Sea - Huang, Ruhui; Xie, Xiaohui; Hu, Jianyu; Sun, Zhenyu (Frontiers in Marine Science, 2021)
One of the main responses of the ocean to typhoons is the generation of near-inertial waves (NIWs), whose intrinsic frequency is close to the local inertial frequency. Based on mooring observations, we carefully investigated the spatial–temporal variations in NIWs in the northern South China Sea (SCS) after Typhoon “Haima”, which passed through the northern SCS from October 20 to 21, 2016, with its track parallel to the mooring array on its northeast side. Moorings in different locations responded differently to this typhoon, with stronger NIWs found on the continental slope to the shelf break and relatively weak NIWs found on the shallow continental shelf. Strong NIWs appeared twice within a short period and showed different characteristics and frequencies. The first NIWs were generated locally with blue-shifted (super-inertial) frequencies. These initial NIWs were dominated by the first three baroclinic modes and rapidly weakened due to their propagation away and local dissipation. However, the second NIWs mainly consisted of higher baroclinic modes with red-shifted (sub-inertial) frequencies. The analysis of the mean background flow revealed that these red-shifted NIWs were excited at low latitudes, and subsequently advected by the poleward background flow to moorings whose latitudes were higher than their critical latitudes. Higher-mode (n > 3) NIWs were more easily carried away by mean background flow, and, at the same time, high-mode NIWs propagated downward to the subsurface layer, leading to the significant elevation of velocity shear therein. Given these findings, the mean background flow may provide an important route to redistributing the energy of the upper ocean imported from typhoons.